Provide a model for predicting emotional divorce based on attachment styles, personality traits, and job self-efficacy through perceived social support in employed married women - Asl, Nahid; Dokanehi Fard, Farideh; Jahangir, Pantea (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to present a model for predicting emotional divorce based on attachment styles, personality traits and job self-efficacy mediated by perceived social support in employed married women. Methods: The method of this research was descriptive-correlational and explanatory with a structural model approach. 400 people were selected from the community of married women working in Tehran Municipality by cluster random sampling method. Guttman Emotional Divorce Questionnaire (2008), Collins and Reed Attachment Questionnaire (1996), NEO-FFI Personality Traits (1985), Job Self-Efficacy Riggs & Knight (1994) and Perceived Social Support Questionnaire (1988) were used to collect data. Results: The results showed that the highest factor load belongs to the indicator of individual consequences (β = 0.882) and the smallest factor load belongs to the indicator of individual beliefs (β = 0.675) job self-efficacy. Thus, considering that the factor loads of all indicators were higher than 0.32, it can be said that all of them have the necessary power to measure the latent variables of the present study. Conclusion: The results showed that according to the obtained results, perceived social support can play a mediating role between emotional divorce, attachment styles, personality traits and job self-efficacy in married working women.